(untitled) (Research, Society and Development, 2022)
Minimum Viable Product is a lean version of the product, also used to synthesize the ideals when building software. This research analyzes the perception of the MVP of students of higher education courses in information technology and future professional software developers. The study aims to demonstrate the knowledge transmitted on this topic in Higher Education Institutions and the gaps in understanding through qualitative-quantitative research with 31 students. This research has an exploratory objective, and the procedure adopted was the survey. The first quantitative result showed that most students already had experience in the job market and or internship. However, when asked about the MVP and its concepts, a considerable portion did not know how to express their ideas. These results can show how the teaching of Software Engineering can be outdated, even though it is essential knowledge in the daily life of professionals and the training of students in the area of Information Technology.